2012
DOI: 10.1007/s00266-012-9977-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported “Worth It” Rating of Aesthetic Surgery in Social Media

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the table of contents or the online instructions to authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…This new and unique connection tool offers a way to disseminate information to a specific audience in real time. Popular examples include Internet forums, weblogs, and social network sites such as Facebook and Twitter [6-7]. Besides social media, the surge in media coverage through TV reality shows, which are programs that film people doing unscripted activities to entertain the public, has changed the perception of ideal beauty standards [8-9].…”
Section: Introductionmentioning
confidence: 99%
“…This new and unique connection tool offers a way to disseminate information to a specific audience in real time. Popular examples include Internet forums, weblogs, and social network sites such as Facebook and Twitter [6-7]. Besides social media, the surge in media coverage through TV reality shows, which are programs that film people doing unscripted activities to entertain the public, has changed the perception of ideal beauty standards [8-9].…”
Section: Introductionmentioning
confidence: 99%
“…On a recent study of aesthetic surgery on RealSelf (RealSelf, Inc.), Domanski and Cavale compared satisfaction rates for popular procedures and found that rhinoplasty had the lowest "Worth It" rating among aesthetic surgical procedures. 27 Dissatisfaction may be due to an inferior aesthetic/functional result or because of unrealistic patient's expectations and inappropriate psychological make up. As most surgeons are not trained in diagnosing psychopathology or assessing emotional stability, and are mostly trained on how and when to operate, the decision when not to operate is often overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Social media has become an important source of information for patients who expect personal medicine with an ongoing patient-physician relationship and instant online availability. 3,13,14 As such, plastic surgeons have begun to adapt and are beginning to operate in this virtual world; however, most of the information on the Internet is far from being dominated by health care providers. For example, only 6% of the posts about plastic surgery on Twitter were published by plastic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that many patients search the web for remedies for their concerns, considering it as the place where an unbiased opinion can be found. 13,14…”
Section: Introductionmentioning
confidence: 99%